STRATEGI PEMASARAN SERAI WANGI DI KECAMATAN GUMAY ULU KABUPATEN LAHAT - Marko ilpiyanto; Nidyawati - (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2022)
The purpose of this study is to identify the marketing tactics that affect citronella grass fragrance sales in the Gumay Ulu District, Lahat Regency, South Sumatra. Interviews and questionnaires were both employed as the primary data gathering methods in this study. The results revealed that capital, labor, raw materials, and time of operation are the factors that have the most impact on the marketing of citronella grass manufacturing in Gumay Ulu District, Lahat Regency. Based on the results of a study, which showed that table t had a value of 1.143,06 while the analysis had a value of 26,00, it can be concluded that some of these elements have a favorable impact on the marketing of fragrant citronella grass in Gumay Ulu District, Lahat Regency. Entrepreneurs of citronella grass are advised to expand capital, enhance the caliber of personnel, and employ premium raw materials in order to improve the results of marketing.